Analisis Yuridis Perbuatan Melawan Hukum Terhadap Dugaan Unsur Penyesatan Dalam Perjanjian Kawin - Delzanty, Kayla; Talitha, Raisyha; Rosdiana, Hani; Ramadhani, Sherlyta; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
A prenuptial agreement serves as a legal instrument that enables spouses to regulate their rights and obligations throughout the course of marriage. However, in practice, such agreements are not immune to legal deviations, particularly regarding the element of misrepresentation which may constitute an unlawful act (onrechtmatige daad). This study aims to provide a juridical analysis of potential misrepresentation in prenuptial agreements and the legal remedies available under Indonesian law. Utilizing a normative legal approach and a case study of Decision Number 526/PDT/G/2012/PN.Jkt.Sel, the research reveals that agreements formed dishonestly and without mutual understanding between the parties may be deemed invalid and annulled by the court. Misrepresentation in this context is considered a defect of consent that violates the principles of honesty and equality in civil contracts. The court's decision highlights that Indonesian law, through civil litigation mechanisms, is capable of offering effective legal protection to aggrieved parties. Consequently, stronger regulation and oversight in the drafting of prenuptial agreements are necessary to ensure the realization of justice and legal certainty.